Analysis of the Short Film "Lights Out": A Semiotic Approach to Cinematic Fear: Analysis of the Short Film "Lights Out": A Semiotic Approach to Cinematic Fear - Pineda, Carlos (Quórum Académico, 2024)
This article aims to analyze the filmic and cinematographic codes used to represent fear in the short film "Lights Out" (2013). The study is based on a theoretical framework supported by prominent semiologists such as, Roland Barthes (1982), Algirdas Julien Greimas (1983), and Umberto Eco (1988). The filmic and cinematographic codes are combined in "Lights Out" (2013) to represent fear, creating a sensory and emotional experience that awakens the deepest fears in the viewer. The analysis also extends to the narrative components, breaking down the structure into three acts and exploring the transformation of the characters, as well as fundamental themes such as fear, survival, and duality.